2022
DOI: 10.1021/acsami.2c18021
|View full text |Cite
|
Sign up to set email alerts
|

Graphite Nanoflake-Modified Mo2C with Ameliorated Interfacial Interaction as an Electrocatalyst for Hydrogen Evolution Reaction

Abstract: Molybdenum carbide (Mo 2 C) is anticipated to be a promising electrocatalyst for electrocatalytic hydrogen production due to its low cost, resourceful property, prominent stability, and Pt-like electrocatalytic activity. The rational design of Mo 2 C-based electrocatalysts is expected to improve hydrogen evolution reaction (HER) performance, especially by constructing ultrasmall Mo 2 C particles and appropriate interfaces. Herein, composites of molybdenum carbide (Mo 2 C) quantum dots anchored on graphite nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
(94 reference statements)
0
6
0
Order By: Relevance
“…However, in MoO 2 /C nanofibers formed under the 20% CO fraction, peaks corresponding to carbide were not observed. Peaks corresponding to Mo 4+ , Mo 5+ , and Mo 6+ are attributed to surface oxidation of carbide, an intrinsic characteristic of Mo carbide. ,, Through XPS depth profiles, it was confirmed that nanostructured carbide undergoes more surface oxidation when exposed to air (Figure S9). Several studies have also noted that nanostructures tend to exhibit surface oxidation due to heightened surface exposure. The surface oxidation effect was also observed in MoCl 5 -based Mo carbide/C nanofibers calcined in an inert gas (Figures S10 and S11).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…However, in MoO 2 /C nanofibers formed under the 20% CO fraction, peaks corresponding to carbide were not observed. Peaks corresponding to Mo 4+ , Mo 5+ , and Mo 6+ are attributed to surface oxidation of carbide, an intrinsic characteristic of Mo carbide. ,, Through XPS depth profiles, it was confirmed that nanostructured carbide undergoes more surface oxidation when exposed to air (Figure S9). Several studies have also noted that nanostructures tend to exhibit surface oxidation due to heightened surface exposure. The surface oxidation effect was also observed in MoCl 5 -based Mo carbide/C nanofibers calcined in an inert gas (Figures S10 and S11).…”
Section: Resultsmentioning
confidence: 93%
“…XPS analysis was conducted to analyze the chemical states of CO–CO 2 calcined Mo compounds/C nanofibers (Figure D,E). In the Mo 3d spectrum, peaks that appeared at 228.3/231.5 eV, corresponding to Mo 2+ , represent the Mo–C bonding in Mo carbide. , Peaks that appeared at 229.4/232.3 eV represent Mo 4+ ; 231.3/234.4 eV represent Mo 5+ ; and 233.2/235.5 eV represent Mo 6+ . , In the C 1s spectrum, 283.6 eV corresponds to Mo–C bonding, while 284.6, 285.8, 286.6, and 288.2 eV correspond to CC, C–C, C–O, and OC–O bonding, respectively. Distinct peaks corresponding to carbide were observed in the Mo 3d and C 1s XPS spectra in samples formed under Ar and above 40% CO fractions.…”
Section: Resultsmentioning
confidence: 99%
“…These peaks exhibit a spin energy separation of 3.1 eV, corresponding to the Mo 3d 5/2 and Mo 3d 3/2 signals of Mo 4+ in MoSe 2 , respectively, while the signal at ∼230.3 corresponds to the Mo–C bonding, indicating a strong coupling between MoSe 2 and carbon matrix . A weak peak ranging from 234.6 to 236.7 eV might be related to the partial surface oxidation of MoSe 2 , which is commonly seen in Mo-based materials, especially for nanomaterials . The Se 3d spectrum is illustrated in Figure b, in which two distinct peaks are evident around 54.4 and 55.3 eV, relating to the Se 3d 5/2 and Se 3d 3/2 signals of Se 2– , respectively …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the Se Auger peaks at 296, 179, and 138 eV, Se 3p 3 peak at 162 eV, along with the Se 3d peak at 55 eV confirm 25 A weak peak ranging from 234.6 to 236.7 eV might be related to the partial surface oxidation of MoSe 2 , which is commonly seen in Mo-based materials, especially for nanomaterials. 26 The Se 3d spectrum is illustrated in Figure 2b, in which two distinct peaks are evident around 54.4 and 55.3 eV, relating to the Se 3d 5/2 and Se 3d 3/2 signals of Se 2− , respectively. 25 Figure 2c illustrates a detailed resolution of the C 1s spectrum, showcasing three distinct peaks at approximately 284.8, 285.8, and 286.8 eV.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, high-performance supported Pt catalysts have alternatively been explored to effectively reduce the Pt usage by dispersing and anchoring the Pt component on supports. Carbon materials with high specific surface area, adjustable porous structure, excellent physicochemical stability, rich natural resources, and low cost have extensively been utilized as carbon supports to prepare efficient Pt/C catalysts. Therefore, preparing new types of high-performance carbon supports is of great significance to achieving future carbon neutrality.…”
Section: Introductionmentioning
confidence: 99%